2017
DOI: 10.1002/ps.4558
|View full text |Cite
|
Sign up to set email alerts
|

Novel nanoscale pheromone dispenser for more accurate evaluation of Grapholita molesta (Lepidoptera: Tortricidae) attract‐and‐kill strategies in the laboratory

Abstract: Incorporation of cypermethrin in nanofibres did not interfere with G. molesta attractiveness. Both aspects of the strategy, the attractant and killing effects, were recorded using innovative nanofibres, and long-term effects suggest a controlled release of pheromone and insecticide. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Nano silica is one such example that is hydrophobic in nature and can absorb into the cuticle layer of the insects upon contact, leading to ultimate death of insects [40]. De Jorge et al [142] showed an excellent effort to explore the importance of nanoformulation in controlled release of AI. They have explored that nanofibers formulation of Grapholita molesta (Lepidoptera:Tortricidae) (Busck) pheromone have no effects on mortality over time, suggesting a controlled release of AI and long-term attract-and-kill effect of pheromone and insecticide.…”
Section: Nanomaterials In Pesticide-based Plant Protectionmentioning
confidence: 99%
“…Nano silica is one such example that is hydrophobic in nature and can absorb into the cuticle layer of the insects upon contact, leading to ultimate death of insects [40]. De Jorge et al [142] showed an excellent effort to explore the importance of nanoformulation in controlled release of AI. They have explored that nanofibers formulation of Grapholita molesta (Lepidoptera:Tortricidae) (Busck) pheromone have no effects on mortality over time, suggesting a controlled release of AI and long-term attract-and-kill effect of pheromone and insecticide.…”
Section: Nanomaterials In Pesticide-based Plant Protectionmentioning
confidence: 99%
“…The notoriety of the nanoscale delivery system in agriculture is due to its improved stability against degradation in the environment. Nanoformulations such as pheromones dispensers have proven to be efficient for prolonged periods in laboratory experiments [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Electrospun fiber is a flexible and functionalized material with large specific surface area, which has great potential in the application of carrier materials. , A small number of researchers have begun to explore the combination of pheromones and electrospun fibers. The research results proved that electrospun fibers loaded with insect sex pheromones can prolong release time for pest control. In our previous research, a biodegradable uniaxial fiber was prepared, which can be effectively used for field control of S. litura . However, as with all existing reports, the monoaxial fibers cannot well solve the problem of burst release of insect sex pheromones.…”
mentioning
confidence: 80%